The International Journal of Universal Multidisciplinary Educational Research Foundation (2020)
This paper is aimed at designing a framework for let-enabled Corruption Management Information System (CMIS') in the Nigerian context. Traditional approaches to fighting corruption have been found to be faulty as a result of not being able to have access to timely and accurate information on the part of the agencies involved, in the process of fighting corruption Having the foregoing as the background, designing a framework for let-enabled Corruption Management Information System (ICT-Enabled CMIS) in Nigeria, is therefore necessary. This initiative will provide real time data for anti-corruption agencies saddled with the responsibility of fighting corruption in order to preserve our democracy. The Proposed System (PS) will ser\>e as an enabler for the anti-corruption management agencies: Economic and Financial Crime Commission (EFCC) and Independent Corrupt Practices Commission (ICPC)) in the daily discharge of their duties. This will be achieved through the provision of user-friendly interfaces, and proper capturing and documentation of information needed as the need arises. Also, the system has a database which will contain the profiles of the citizens. The homepage where ah interfaces can be navigated is also provided for queries to be answered w hen the need arises. Finally, summary, conclusion and recommendations are made. Keywords: Information and Communications Technology (ICT), Corruption, Corruption Management Information System (CMIS), Corruption Management (CM),